Impact of kelp cultivation on the Ecological Status of benthic habitats and Zostera marina seagrass biomass. Issue 1 (15th October 2017) - Walls, A.M.; Kennedy, R.; Edwards, M.D.; Johnson, M.P.
Abstract: The Ecological Status of subtidal benthic communities within a commercial kelp farm on the southwest coast of Ireland was not impacted by macroalgal cultivation. Additionally, there was no effect on the biomass of Zostera marina, a key habitat under the EU Habitats Directive and OSPAR Commission. However, sediment grain size and total organic matter (TOM) were influenced by abiotic and biotic aspects of the farm. A temporal effect on univariate and multivariate species data, Infaunal Quality Index (IQI) and Z. marina biomass was observed. This effect was likely a community response to high storm disturbance in winter 2013/14. The use of IQI to assess the impact of macroalgal cultivation on benthic communities is a novel approach. This study supports a view that environmental impacts of macroalgal cultivation are relatively benign compared to other forms of aquaculture. Further research must be conducted to understand all interactions between aquaculture activities and the environment. Highlights: Macroalgal kelp cultivation showed little impact on subtidal benthic communities. The Ecological Status of communities improved over the duration of the study showing a temporal shift. This shift is likely a community response to severe storm disturbance in winter 2013/14. Particle size and total organic matter content of the sediment were impacted by the farm. The presence of the farm did not impact Zostera marina biomass values.